Cinema, if you please : the memory of taste, the taste of memory - Pomerance, Murray, 1946- (Edinburgh University Press, 2018)
In Cinema, If You Please, Murray Pomerance explores our ways of watching film in light of socially organized forms of pleasure that date back to the seventeenth and eighteenth centuries.